Observations on the Effect of Diet on Shell Coloration in the Donkey's Ear Abalone, Haliotis Asinina Linne - Capinpin, Emmanuel C. (Silliman Journal, 2023)
Shell color was determined by the food eaten by the Donkey's ear abalone, Haliotis asinina. Shells of abalone juveniles fed with two cultured red seaweed, Gracilariopsis heteroclada and Kappaphycus alvarezii were dark brown in color as compared to light bluish-green in juveniles fed with an artificial feed. The use of this artificial feed for cultured abalone to produce the light bluish-green color is suggested as a biological tag for field growth and reseeding experiments.